Curcumin Administered in Combination with Glu-GNPs Induces Radiosensitivity in Transplanted Tumor MDA-MB-231-luc Cells in Nude Mice. (16th November 2021) - Li, Mengjie; Lin, Ling; Guo, Tingting; Wu, Yujian; Lin, Jiayi; Liu, Yuanyuan; Yang, Ke; Hu, Chenxia
Abstract : Curcumin is a type of plant polyphenol extracted from Curcuma longa L. rhizome, which demonstrates antitumor activity in breast cancer cells in vitro . To investigate the combined effect and possible mechanism of curcumin and glucose-gold nanoparticles (Glu-GNPs), the radiosensitivity of breast carcinoma xenografts was assessed in nude mice. MDA-MB-231 cells labeled with firefly luciferase were inoculated into the mammary fatty pads of nude mice to establish a transplantation tumor model of human breast cancer. The tumor-bearing mice were treated with different drugs (curcumin, Glu-GNPs, and cisplatin) for 3 weeks prior to radiotherapy. The body weights and tumor volumes of the mice were measured in regular intervals. Tumor bioluminescence intensity was determined in real-time using an in vivo bioluminescence imaging system to monitor tumor growth. Transplanted tumor tissue samples were taken for hematoxylin and eosin (HE) staining, and the expression of VEGF, HSP90, HIF-1 α, and MMP9 was evaluated via reverse transcription-quantitative PCR or immunohistochemistry. The results revealed that the breast tumor-bearing nude mouse model was successfully established, as evidenced by a stable expression of luciferase. Curcumin inhibited the growth of tumors without causing significant weight loss in mice. Furthermore, additive inhibition was demonstrated when curcumin was administered in combination with Glu-GNPs and irradiation. Tumor bioluminescence intensity was decreased in the model group following curcumin, Glu-GNPs, and irradiation treatment. HE staining demonstrated that transplanted tumors were malignant, with necrotic tissue exhibited centrally. It was concluded that curcumin administered in combination with Glu-GNPs and X-ray irradiation could reduce the protein expression of VEGF, HSP90, HIF-1 α, and MMP9 in tumor tissue when compared with the model group. Curcumin and Glu-GNPs administered with X-ray irradiation significantly inhibited tumor growth and induced radiosensitivity, which may be associated with the inhibition of angiogenesis in tumor tissue.